Processing of Salted Eggs of various flavors with Optimization of Duck Egg Production in Mompang Village - Harahap, Nurainun; Santi, Melia Afnida; Faradillah, Fira (Talenta Publisher Universitas Sumatera Utara, 2018)
The community service was conducted in Mompang Village, Padangsidimpuan District, Angkola Julu. This ac tivity aims to increase public knowledge and produce innovations in the processing of poultry production. Eggs are one of the livestock products that are easily damaged in storage and have a fishy taste, especially duck eggs. The used of natural salt and spices can produce salted eggs with a variety of aromas such as soto flavor, rendang and spicy so as to reduce fishy smell and increase egg retention. This activity was held on July 15, 2018 which was attended by 22 participants. The method used was the socialization and demonstration of making various salted roasted eggs. Based on the results of organoleptic testing, making various salted eggs is quite good to reduce the fishy flavor contained in duck eggs so that it can increase the amount of consumption, with this activity can increase public knowledge about processing livestock products.